2015
DOI: 10.12688/f1000research.7340.1
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization estimates of the global and regional disease burden of four foodborne chemical toxins, 2010: a data synthesis

Abstract: Background Chemical exposures have been associated with a variety of health effects; however, little is known about the global disease burden from foodborne chemicals. Food can be a major pathway for the general population’s exposure to chemicals, and for some chemicals, it accounts for almost 100% of exposure.  Methods and Findings Groups of foodborne chemicals, both natural and anthropogenic, were evaluated for their ability to contribute to the burden of disease.  The results of the analyses on four chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…Africa and Asia continue to be the leading continents in terms of new cases recorded each year, with 64,779 (7.7%) and 609,596 (72%) cases respectively, together representing about 80% of the total cases in the world. Aflatoxin B1 alone was estimated to cause 25,200 to 155,000 cases each year [10,11], 40% of which occur in sub-Saharan Africa only [2] where aflatoxin-induced liver cancer accounts for one-third of all liver cancer cases recorded in the whole African continent [12]. At the country level, China has the highest incidence of liver cancer in the world, with the vast majority being recorded in the Southern part of the country where the two main synergistic causative agents, exposure to dietary aflatoxins and HB chronic infections, are endemic and highest [3].…”
Section: Chronic Diseases Caused By Aflatoxinsmentioning
confidence: 99%
“…Africa and Asia continue to be the leading continents in terms of new cases recorded each year, with 64,779 (7.7%) and 609,596 (72%) cases respectively, together representing about 80% of the total cases in the world. Aflatoxin B1 alone was estimated to cause 25,200 to 155,000 cases each year [10,11], 40% of which occur in sub-Saharan Africa only [2] where aflatoxin-induced liver cancer accounts for one-third of all liver cancer cases recorded in the whole African continent [12]. At the country level, China has the highest incidence of liver cancer in the world, with the vast majority being recorded in the Southern part of the country where the two main synergistic causative agents, exposure to dietary aflatoxins and HB chronic infections, are endemic and highest [3].…”
Section: Chronic Diseases Caused By Aflatoxinsmentioning
confidence: 99%
“…On the other hand, continuous daily exposure to single or mixtures of these food contaminants via consumption of contaminated RTEs could produce a plethora of adverse health effects. Observable effects may range from mild to recurrent nausea, vomiting, and diarrhea (Ceuppens et al., ) to severe complications such as cancers, neural tube defects, and even human fatalities (Gibb et al., ; IARC, ; JECFA, , ; Kamala et al., ; Wild & Gong, ). Thus, improperly prepared RTEs in LMICs, where regulations and monitoring for compliance are grossly inadequate, may constitute a huge risk to public health.…”
Section: Introductionmentioning
confidence: 99%
“…To date, it is estimated that at least 500 million of people living in sub-Saharan Africa, Latin America and Asia, are exposed to increasing levels of mycotoxins, including aflatoxins, through contaminated commodities (Pitt et al, 2012). In 2010, analysis of several foodborne chemicals by the Chemical and Toxins Disease Task Force reported that aflatoxin was associated with the highest number of DALYs (deaths and disability adjusted life years) (636,869) where one DALY represents the sum of years lived with disability and years of life lost (Gibb et al, 2015). Worryingly, surveys demonstrated that higher levels of aflatoxins in agricultural commodities were linked to upraising climatic conditions (Streit et al, 2013).…”
Section: Introductionmentioning
confidence: 99%